Penguatan Moderasi Beragama Melalui Optimalisasi Manajemen Evaluasi Pendidikan Agama Islam di Sekolah Dasar - Asraf Kurnia; Ahmad Sabri; Remiswal; Heri Effendi; Muspardi (Institut Muslim Cendekia, 2024)
This article discusses the importance of strengthening religious moderation through the optimization of evaluation management in Islamic Religious Education (PAI) at the elementary school level. The aim of this research is to identify and explain strategies that can be used to optimize PAI evaluation management in shaping religious moderation attitudes among elementary school students. This study is an effort to address the challenges of radicalization and intolerance that are developing among the younger generation, as well as to ensure that religious education can produce individuals who are tolerant, just, and balanced in interacting within a diverse society. The research method used in this study is a literature review, which aims to collect, analyze, and synthesize information from various sources related to evaluation management in PAI and religious moderation. The findings of this research indicate that evaluations in PAI are not only intended to measure religious knowledge but also to assess students' religious moderation attitudes. Effective evaluations can be carried out through authentic approaches, such as the use of attitude assessment rubrics, observations, group discussions, and attitude-based projects. Furthermore, the study highlights the importance of evaluation planning that integrates religious moderation indicators and follow-up evaluations through extracurricular activities that support tolerance values. The findings suggest that strengthening religious moderation through PAI evaluations can help shape students into more tolerant and just individuals.